The spiFEG Locus in Streptococcus infantarius subsp. infantarius BAA-102 Confers Protection against Nisin U - Draper, Lorraine A. (American Society for Microbiology, 2012)
Nisin U is a member of the extended nisin family of lantibiotics. Here we identify the presence of nisin U immunity gene homologues in Streptococcus infantarius subsp. infantarius BAA-102. Heterologous expression of these genes in Lactococcus lactis subsp. cremoris HP confers protection to nisin U and other members of the nisin family, thereby establishing that the recently identified phenomenon of resistance through immune mimicry also occurs with respect to nisin.